Genetic variation in packed red cell volume and frequency of parasitaemia in East African Zebu cattle exposed to drug-resistant trypanosomes - Rowlands, G.J.; Mulatu, W.; Nagda, S.M.; Dolan, R.B.; D'Ieteren, G.D.M. (Elsevier, 1995)
Nine hundred and thirty-six East African Zebu village calves in an area of high trypanosomiasis risk in south-western Ethiopia were monitored monthly with their dams from birth to 3 years of age. Mean packed red cell volume (PCV) and the frequency of detected parasitaemia were calculated for each offspring and its dam measured simultaneously over 6 month `wet' and `dry' seasons from March 1986 to February 1992. Six-month residual values for offspring, corrected for solutions of fixed environmental effects, herd, year, season, etc., estimated by least squares analysis of variance, were regressed against corresponding residual values for their dams. The common environment component of variance, not already corrected for and remaining in these residual values, was estimated by regression of offspring values against those for the cows that gave birth closest to the offspring's own date of birth. When corrected for this component, offspring-dam regression coefficients for mean PCV, averaged over calves for each dam, were found to increase from 0.08 + 0.05 (SE) to 0.26 + 0.06 from 4 to 21 months of age. When also corrected for frequency of parasitaemia and treatment, regression coefficients were reduced, but the increasing trend with age was maintained. Offspring-dam regression coefficients for frequency of parasitaemia showed, if anything, an opposite trend. Application of an `animal model' to offspring over 21 months of age and their dams gave heritability estimates of 0.32 + 0.07 for PCV, 0.18 + 0.07 for PCV, corrected for frequency of parasitaemia, and 0.08 + 0.05 for frequency of parasitaemia.